High-viscosity flame-retardant adhesive and preparation method thereof
By using boric acid modified epoxy resin and sulfur-containing flame retardant components in the adhesive, the insulation layer and carbonized layer are formed, which solves the problems of insufficient viscosity and poor flame retardant effect, and achieves high viscosity and good resistance The combustion performance ensures the safety of the material in fire.
Patent Information
- Application Number
- CN202411632653.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing adhesives are not sticky when connecting objects, and have poor flame retardant effects during fire, which poses safety hazards.
8-12 parts by weight of boric acid modified epoxy resin, 6-10 parts by weight of sulfur flame retardant, 10-20 parts by weight of butyl rubber, 5-8 parts by weight of polyvinyl alcohol and 1-2 parts by weight of The antioxidant GSC-627 is prepared by a specific synthetic method to prepare a high viscosity flame retardant adhesive, forming a glass-like coating and a carbonized layer to isolate oxygen and heat, and improve flame retardant performance.
High viscosity and good flame retardant effect are achieved, ensuring the safety of the material in fire situations, and improving viscosity and peel strength through the crosslinked structure.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesives, in particular to a high-viscosity flame-retardant adhesive and a preparation method thereof. Background Art
[0002] Adhesive is a substance that can connect objects of the same or different materials. It is widely used in daily life and modern industry. The adhesives currently on the market have the problem of insufficient viscosity, resulting in poor connection between objects, and the flame retardant effect is not very good in case of fire, which will lead to safety hazards. For example, patent CN102676090A discloses an adhesive, which is prepared by emulsion copolymerization of multiple acrylic acid monomers and vinyl acetate monomers. It has good adhesion and stability and can replace natural latex as an adhesive for recycled leather soles. It can make the recycled leather have good tensile strength and folding strength, but the flame retardant effect is not improved. Summary of the invention
[0003] 1. Technical issues to be resolved In view of the deficiencies in the prior art, the present invention provides a high-viscosity flame-retardant adhesive and a preparation method thereof, which has good flame retardancy and high viscosity.
[0004] (II) Technical solution To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a high-viscosity flame-retardant adhesive, comprising the following weight components: 8-12 weight parts of boric acid-modified epoxy resin, 6-10 weight parts of sulfur-containing flame retardant, 10-20 weight parts of butyl rubber, 5-8 weight parts of polyvinyl alcohol, and 1-2 weight parts of antioxidant GSC-627.
[0005] Preferably, the preparation method of the boric acid modified epoxy resin is: (1) Add (dimethylaminomethyl)phenol and boric acid to toluene solvent, stir and disperse, react at 45-60°C for 10-14h, and then remove the solvent by distillation under reduced pressure, wash with distilled water, and dry to obtain phenol-modified boric acid; (2) adding 8-15 parts by weight of phenol-modified boric acid and 7-12 parts by weight of 6-chloro-1-hexene into a reactor filled with N,N-dimethylformamide solvent, stirring and dissolving, reacting at 85-100° C., and then distilling under reduced pressure, washing with petroleum ether, and drying to obtain olefinated boronic acid; (3) adding 5-10 parts by weight of olefinated boronic acid to an ethanol solvent, stirring evenly, and then adding 4-8 parts by weight of an aqueous hydrogen peroxide solution, stirring and reacting for 3-5 hours, and then standing and extracting, taking the organic phase, drying it, and distilling it under reduced pressure to obtain epoxy boronic acid; (4) Add 5-8 parts by weight of bisphenol A, 4-6 parts by weight of epoxyboric acid, 4-10 parts by weight of allyl alcohol glycidyl ether, 6-8 parts by weight of glycidyl acrylate and 1-2 parts by weight of chloroplatinic acid into a reactor, react for 8-12 hours, and wash with water until neutral to obtain a boric acid-modified epoxy resin.
[0006] Preferably, the mass ratio of (dimethylaminomethyl)phenol to boric acid in (1) is 1:0.4-0.6.
[0007] Preferably, the reaction time in (2) is 7-14 hours.
[0008] Preferably, the reaction temperature in (3) is 20-26°C.
[0009] Preferably, the reaction temperature in (4) is 60-85°C.
[0010] Preferably, the preparation method of the sulfur-containing flame retardant is: add 8-10 parts by weight of olefinated boric acid to N,N-dimethylformamide solvent, stir to dissolve, then continue to add 6-12 parts by weight of 3-(dimethylamino)-1-propanethiol and 0.8-1 parts by weight of benzoin dimethyl ether initiator, irradiate with 365nm ultraviolet light at 40-55°C for 2-6h, centrifuge, wash and dry after completion to obtain the sulfur-containing flame retardant.
[0011] Preferably, the preparation method of the high-viscosity flame retardant adhesive is: adding boric acid-modified epoxy resin, sulfur-containing flame retardant, butyl rubber, polyvinyl alcohol, and antioxidant GSC-627 into a reactor, heating the reaction at 102-110° C. for 3-6 hours, and obtaining the high-viscosity flame retardant adhesive after the reaction.
[0012] 3. Beneficial technical effects The invention adds boric acid-modified epoxy resin, sulfur-containing flame retardant, butyl rubber, polyvinyl alcohol and antioxidant GSC-627 into a reactor, heats the reaction and obtains a high-viscosity flame retardant adhesive after the reaction is completed.
[0013] Boric acid in boric acid-modified epoxy resin and sulfur-containing flame retardant can form a glass-like coating at high temperature, covering the polymer surface, isolating the air, forming a protective layer to isolate oxygen and heat, and achieving a good flame retardant effect. The sulfur element contained in the sulfur-containing flame retardant will promote the formation of a carbonized layer on the polymer surface when it burns. This carbonized layer can effectively isolate oxygen and external heat, thereby protecting the internal polymer from further combustion and achieving a flame retardant effect. The epoxy group in the boric acid-modified epoxy resin can react with the hydroxyl group in polyvinyl alcohol through a ring-opening reaction. It not only reacts with the hydroxyl group in polyvinyl alcohol, but also reacts with the amino group in the sulfur-containing flame retardant to form a network solid, forming a stronger cross-linking structure, making it more viscous. DETAILED DESCRIPTION
[0014] Example 1
[0015] (1) Add (dimethylaminomethyl)phenol and boric acid to a toluene solvent, wherein the mass ratio of (dimethylaminomethyl)phenol to boric acid is 1:0.4, stir and disperse, react at 45°C for 10 hours, and then remove the solvent by distillation under reduced pressure, wash with distilled water, and dry to obtain phenol-modified boric acid; (2) 8 parts by weight of phenol-modified boric acid and 7 parts by weight of 6-chloro-1-hexene were added to a reactor filled with N,N-dimethylformamide solvent, stirred to dissolve, and reacted at 85° C. for 7 h. After the reaction, the mixture was distilled under reduced pressure, washed with petroleum ether, and dried to obtain olefinated boronic acid; (3) Add 5 parts by weight of olefinated boronic acid to an ethanol solvent, stir evenly, then add 4 parts by weight of an aqueous hydrogen peroxide solution, stir and react at 20° C. for 3 hours, let stand after reaction, extract, take the organic phase, dry it, and distill it under reduced pressure to obtain epoxy boronic acid; (4) adding 5 parts by weight of bisphenol A, 4 parts by weight of epoxyboric acid, 4 parts by weight of allyl alcohol glycidyl ether, 6 parts by weight of glycidyl acrylate and 1 part by weight of chloroplatinic acid into a reactor, reacting at 60° C. for 8 hours, washing with water until neutral, and obtaining a boric acid-modified epoxy resin; (5) Add 8 parts by weight of olefinated boric acid to N,N-dimethylformamide solvent, stir to dissolve, then continue to add 6 parts by weight of 3-(dimethylamino)-1-propanethiol and 0.8 parts by weight of benzoin dimethyl ether initiator, irradiate with 365 nm ultraviolet light at 40° C. for 2 h, centrifuge, wash and dry after the end to obtain a sulfur-containing flame retardant; (6) 8 parts by weight of boric acid-modified epoxy resin, 6 parts by weight of sulfur-containing flame retardant, 10 parts by weight of butyl rubber, 5 parts by weight of polyvinyl alcohol, and 1 part by weight of antioxidant GSC-627 were added into a reactor and heated at 102° C. for 3 hours to obtain a high-viscosity flame retardant adhesive.
[0016] Example 2
[0017] (1) Add (dimethylaminomethyl)phenol and boric acid to a toluene solvent, wherein the mass ratio of (dimethylaminomethyl)phenol to boric acid is 1:0.6, stir and disperse, react at 60°C for 14 hours, and then remove the solvent by distillation under reduced pressure, wash with distilled water, and dry to obtain phenol-modified boric acid; (2) adding 15 parts by weight of phenol-modified boric acid and 12 parts by weight of 6-chloro-1-hexene into a reactor filled with N,N-dimethylformamide solvent, stirring to dissolve, reacting at 100° C. for 14 h, and then distilling under reduced pressure, washing with petroleum ether, and drying to obtain olefinated boronic acid; (3) adding 10 parts by weight of olefinated boronic acid to an ethanol solvent, stirring evenly, and then adding 8 parts by weight of an aqueous hydrogen peroxide solution, stirring and reacting at 26° C. for 5 hours, standing and extracting after the reaction, drying the organic phase, and distilling under reduced pressure to obtain epoxy boronic acid; (4) adding 8 parts by weight of bisphenol A, 6 parts by weight of epoxyboric acid, 10 parts by weight of allyl alcohol glycidyl ether, 8 parts by weight of glycidyl acrylate and 2 parts by weight of chloroplatinic acid into a reactor, reacting at 85° C. for 12 hours, and washing with water until neutral to obtain a boric acid-modified epoxy resin; (5) Add 10 parts by weight of olefinated boric acid to N,N-dimethylformamide solvent, stir to dissolve, then continue to add 12 parts by weight of 3-(dimethylamino)-1-propanethiol and 1 part by weight of benzoin dimethyl ether initiator, irradiate with 365 nm ultraviolet light at 55° C. for 6 h, centrifuge, wash and dry after the end to obtain a sulfur-containing flame retardant; (6) 10 parts by weight of boric acid-modified epoxy resin, 8 parts by weight of sulfur-containing flame retardant, 15 parts by weight of butyl rubber, 8 parts by weight of polyvinyl alcohol, and 2 parts by weight of antioxidant GSC-627 were added into a reactor, and heated at 110° C. for 6 hours to obtain a high-viscosity flame retardant adhesive.
[0018] Example 3
[0019] (1) Add (dimethylaminomethyl)phenol and boric acid to a toluene solvent, wherein the mass ratio of (dimethylaminomethyl)phenol to boric acid is 1:0.5, stir and disperse, react at 52.5°C for 12 hours, and then remove the solvent by reduced pressure distillation, wash with distilled water, and dry to obtain phenol-modified boric acid; (2) adding 11.5 parts by weight of phenol-modified boric acid and 9.5 parts by weight of 6-chloro-1-hexene into a reactor filled with N,N-dimethylformamide solvent, stirring to dissolve, reacting at 92.5° C. for 10.5 hours, and then distilling under reduced pressure, washing with petroleum ether, and drying to obtain olefinated boronic acid; (3) adding 7.5 parts by weight of olefinated boronic acid to an ethanol solvent, stirring evenly, and then adding 6 parts by weight of an aqueous hydrogen peroxide solution, stirring and reacting at 23° C. for 4 hours, and then standing and extracting. The organic phase is dried and distilled under reduced pressure to obtain epoxy boronic acid; (4) adding 6.5 parts by weight of bisphenol A, 5 parts by weight of epoxyboric acid, 7 parts by weight of allyl alcohol glycidyl ether, 7 parts by weight of glycidyl acrylate and 1.5 parts by weight of chloroplatinic acid into a reactor, reacting at 72.5° C. for 10 hours, and washing with water until neutral to obtain a boric acid-modified epoxy resin; (5) Add 9 parts by weight of olefinated boric acid to N,N-dimethylformamide solvent, stir to dissolve, then continue to add 9 parts by weight of 3-(dimethylamino)-1-propanethiol and 0.9 parts by weight of benzoin dimethyl ether initiator, irradiate with 365 nm ultraviolet light at 47.5° C. for 4 h, centrifuge, wash and dry to obtain a sulfur-containing flame retardant; (6) 10 parts by weight of boric acid-modified epoxy resin, 8 parts by weight of sulfur-containing flame retardant, 15 parts by weight of butyl rubber, 6.5 parts by weight of polyvinyl alcohol, and 1.5 parts by weight of antioxidant GSC-627 were added into a reactor, and heated at 106° C. for 4.5 hours to obtain a high-viscosity flame retardant adhesive.
[0020] Comparative Example 1 (1) Add 9 parts by weight of olefinated boric acid to N,N-dimethylformamide solvent, stir to dissolve, then continue to add 9 parts by weight of 3-(dimethylamino)-1-propanethiol and 0.9 parts by weight of benzoin dimethyl ether initiator, irradiate with 365 nm ultraviolet light at 47.5° C. for 4 hours, centrifuge, wash and dry after completion to obtain a sulfur-containing flame retardant; (2) 8 parts by weight of a sulfur-containing flame retardant, 15 parts by weight of butyl rubber, 6.5 parts by weight of polyvinyl alcohol, and 1.5 parts by weight of an antioxidant GSC-627 were added to a reactor, and the mixture was heated at 106° C. for 4.5 hours to obtain a highly viscous flame retardant adhesive.
[0021] Comparative Example 2 (1) Add (dimethylaminomethyl)phenol and boric acid to a toluene solvent, wherein the mass ratio of (dimethylaminomethyl)phenol to boric acid is 1:0.5, stir and disperse, react at 52.5°C for 12 hours, and then remove the solvent by reduced pressure distillation, wash with distilled water, and dry to obtain phenol-modified boric acid; (2) adding 11.5 parts by weight of phenol-modified boric acid and 9.5 parts by weight of 6-chloro-1-hexene into a reactor filled with N,N-dimethylformamide solvent, stirring to dissolve, reacting at 92.5° C. for 10.5 hours, and then distilling under reduced pressure, washing with petroleum ether, and drying to obtain olefinated boronic acid; (3) adding 7.5 parts by weight of olefinated boronic acid to an ethanol solvent, stirring evenly, and then adding 6 parts by weight of an aqueous hydrogen peroxide solution, stirring and reacting at 23° C. for 4 hours, and then standing and extracting. The organic phase is dried and distilled under reduced pressure to obtain epoxy boronic acid; (4) adding 6.5 parts by weight of bisphenol A, 5 parts by weight of epoxyboric acid, 7 parts by weight of allyl alcohol glycidyl ether, 7 parts by weight of glycidyl acrylate and 1.5 parts by weight of chloroplatinic acid into a reactor, reacting at 72.5° C. for 10 hours, and washing with water until neutral to obtain a boric acid-modified epoxy resin; (5) 10 parts by weight of boric acid-modified epoxy resin, 15 parts by weight of butyl rubber, 6.5 parts by weight of polyvinyl alcohol, and 1.5 parts by weight of antioxidant GSC-627 were added into a reactor, and heated at 106° C. for 4.5 hours to obtain a high-viscosity flame-retardant adhesive.
[0022] Use an oxygen index meter to test the limiting oxygen index of the adhesive; use a horizontal and vertical combustion instrument to test the combustion level of the adhesive.
[0023] Table 1: Tests of flame retardancy.
[0024]
[0025] As can be seen from Table 1, the high-viscosity flame-retardant adhesives prepared in Examples 1-3 of the present invention have better flame retardant effects than those prepared in Comparative Examples 1-2; Comparative Example 1 does not add boric acid-modified epoxy resin, and Comparative Example 2 does not add sulfur-containing flame retardant, so the flame retardant effects are poorer than those of Examples 1-3.
[0026] The peel strength was measured in accordance with the national standard GB / T2794-1995. The test method was as follows: a high-viscosity flame-retardant adhesive was applied to the calcium-plastic corrugated paper, and then the corrugated paper was covered on the calcium-plastic corrugated paper. After standing for 24 hours, a WZL-300 horizontal computer tensile tester was used to measure the 180° peel strength of the material to be tested. The test results are shown in Table 2.
[0027] Table 2: Peel strength test.
[0028]
[0029] As can be seen from Table 2, the high-viscosity flame retardant adhesives prepared in Examples 1-3 of the present invention have better peel strength than those prepared in Comparative Examples 1-2, indicating that the viscosity is higher; the peel strength of Comparative Example 2 is higher than that of Comparative Example 1, because Comparative Example 2 has a large number of epoxy groups, which can react with the hydroxyl groups in polyvinyl alcohol to form a network cured product and a high cross-linked structure, which exhibits better viscosity; the epoxy groups contained in Examples 1-3 not only react with the hydroxyl groups in polyvinyl alcohol, but also react with the amino groups in the sulfur-containing flame retardant to form a stronger cross-linked structure, making it more viscous.
[0030] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A high-viscosity flame-retardant adhesive, characterized in that: The invention comprises the following components by weight: 8-12 parts by weight of boric acid modified epoxy resin, 6-10 parts by weight of sulfur-containing flame retardant, 10-20 parts by weight of butyl rubber, 5-8 parts by weight of polyvinyl alcohol, and 1-2 parts by weight of antioxidant GSC-627; The preparation method of the boric acid modified epoxy resin is: (1) Add (dimethylaminomethyl)phenol and boric acid to toluene solvent, stir and disperse, react at 45-60°C for 10-14h, and then remove the solvent by distillation under reduced pressure, wash with distilled water, and dry to obtain phenol-modified boric acid; (2) adding 8-15 parts by weight of phenol-modified boric acid and 7-12 parts by weight of 6-chloro-1-hexene into a reactor filled with N,N-dimethylformamide solvent, stirring and dissolving, reacting at 85-100° C., and then distilling under reduced pressure, washing with petroleum ether, and drying to obtain olefinated boronic acid; (3) adding 5-10 parts by weight of olefinated boronic acid to an ethanol solvent, stirring evenly, and then adding 4-8 parts by weight of an aqueous hydrogen peroxide solution, stirring and reacting for 3-5 hours, and then standing and extracting, taking the organic phase, drying it, and distilling it under reduced pressure to obtain epoxy boronic acid; (4) Add 5-8 parts by weight of bisphenol A, 4-6 parts by weight of epoxyboric acid, 4-10 parts by weight of allyl alcohol glycidyl ether, 6-8 parts by weight of glycidyl acrylate and 1-2 parts by weight of chloroplatinic acid into a reactor, react for 8-12 hours, and wash with water until neutral to obtain a boric acid-modified epoxy resin.
2. The high-viscosity flame-retardant adhesive according to claim 1, characterized in that: The mass ratio of (dimethylaminomethyl)phenol to boric acid in (1) is 1:0.4-0.
6.
3. The high-viscosity flame-retardant adhesive according to claim 1, characterized in that: The reaction time in (2) is 7-14 hours.
4. The high-viscosity flame-retardant adhesive according to claim 1, characterized in that: The reaction temperature in (3) is 20-26°C.
5. The high-viscosity flame-retardant adhesive according to claim 1, characterized in that: The reaction temperature in (4) is 60-85°C.
6. The high-viscosity flame-retardant adhesive according to claim 1, characterized in that: The preparation method of the sulfur-containing flame retardant comprises the following steps: adding 8-10 parts by weight of olefinated boric acid to an N,N-dimethylformamide solvent, stirring and dissolving the solvent, then continuously adding 6-12 parts by weight of 3-(dimethylamino)-1-propanethiol and 0.8-1 parts by weight of benzoin dimethyl ether initiator, irradiating the solvent with 365 nm ultraviolet light at 40-55° C. for 2-6 hours, centrifuging, washing and drying the solvent after the solvent is irradiated, and the sulfur-containing flame retardant is obtained.
7. A method for preparing a high-viscosity flame-retardant adhesive as claimed in any one of claims 1 to 6, characterized in that: The preparation method of the high-viscosity flame-retardant adhesive is as follows: boric acid-modified epoxy resin, sulfur-containing flame retardant, butyl rubber, polyvinyl alcohol, and antioxidant GSC-627 are added into a reactor, and heated at 102-110° C. for reaction for 3-6 hours, and then the high-viscosity flame-retardant adhesive is obtained.
Citation Information
Patent Citations
High-viscosity flame-retardant adhesive and preparation method thereof
CN104774577A
Flame retardant butyl pressure sensitive adhesive
CN110295020A
Flame-retardant heat-insulating butyl rubber self-adhesive waterproof coiled material
CN117417702A
Preparation process of temperature-resistant and shear-resistant fracturing fluid tackifier
CN117736127A
Preparation method of rubber strip applied to rubber coating and sealing of roller
CN118146742A
Cited By
Antibacterial material applied to linen fabric and preparation method of antibacterial material
CN119932911A
